Health Effects Associated With Kratom () and Polysubstance Use: A Narrative Review - Catherine W Striley; Carolin C Hoeflich; Andrew T Viegas; Lindsey A Berkowitz; Emily G Matthews; Leyla P Akin; Chidinma Iheanyi-Okeahialam; Urmeen Mansoor; Christopher R McCurdy (SAGE Publishing, 2022)
Background: Kratom ( Mitragyna speciosa ) consumption and associated health effects have raised debates in the United States. Although most people using this herb do not experience adverse health effects associated with kratom use, medical providers should be knowledgeable of emerging substances and concurrent, sequential, or simultaneous use of other drugs which may impact healthcare recommendations and prescribing practices. Methods: The objective of this narrative review was to elucidate selected health effects associated with using kratom-either alone or with other substances. Since scientifically controlled human subjects research on kratom use is still limited, relevant case reports were also described. Results: Cardiovascular, gastrointestinal, neurological, and psychiatric effects associated with kratom use were especially notable, and in-utero exposure accompanied concern regarding a neonate's risk for developing neonatal abstinence syndrome. Our ability to identify and understand the role of this herb in kratom-associated fatalities is complicated since kratom is not routinely screened for in standard forensic toxicology. If a screening is performed, it is usually for the major alkaloid, mitragynine, as a surrogate for kratom use. In addition to lacking a standard practice of screening decedents for kratom alkaloids, the association between mortality and kratom use may be confounded by polysubstance use, adulteration of kratom products, and drug-herb interactions. Conclusions: Increasing medical awareness of this herb is vital to ensuring prompt administration of best-practice medical advice or treatment for people seeking information related to kratom use or for patients experiencing an adverse health effect that may be associated with using or withdrawing from kratom. Knowledge gained from continued surveillance and study of kratom and its associated health effects may assist in guiding clinical decision-making and preventing development of adverse health effects among people using kratom.